Further contribution to cytotaxonomy of the genus Silene L. (Sect. Auriculatae, Caryophyllaceae) - Gholipour, Abbas; Sheidai, Masoud (Acta Biologica Szegediensis, 2010)
The present study reports the chromosome numbers of 18 Silene L. species subspecies and varieties from the sect. Auriculatae for the first time. S. commelinifolia var. isophylla, S. commelinifoilia var. ovatifolia, S. araratica, S. meyeri ssp. persica, S. nizvana, S. oligophylla, S. persica and S. rhynchocarpa showed 2n = 2x = 24 chromosome number, S. pseudoaucheriana,S. gynodioica, S. erysimifolia, S. guntensis, S. goniocaula, S. lucida S. microphylla showed 2n= 4x= 48 and S. hirticalyx had 2n=6x=72 chromosome number. The size of the chromosomes varied from 1.53 μm in Ahvan population of S. commelinifolia var. commelinifolia to 4.97 μm in S. oligophylla. The chromosomes were metacentric (m) and sub-metacentric (sm). The species studied differed significantly in total size of the chromosomes, size of the short arms and the long arms indicating the role of quantitative changes of chromosomes in species diversification. The Silene species differed in karyotype formulae and symmetry indicating qualitative changes in the chromosomes possibly due to the occurrence of structural changes. Different clustering and ordination methods showed karyotype distinctness of the species studied.